From sharing to profiting: Exploring the interplay between value creation and strategic appropriation in data ecosystems - Manuel Trenz (Electronic Markets, 2025)
This study explores the interdependency between collaborative value creation and value appropriation within data ecosystems, focusing on how organizations can effectively share and utilize data for mutual benefits. It examines the factors that influence the capacity to create value from shared data and the strategies for appropriating value from such data sharing. Through qualitative analysis of a healthcare data ecosystem, the research identifies key determinants of value creation capacity and outlines four central elements of value appropriation strategies (VAS): selective partnering, data tailoring, benefit safeguarding, and control enforcement. The findings reveal how shared data's latent potential interacts with an actor's potential to foster value creation capacity, while also highlighting the interdependencies between these concepts and VAS. This study contributes to understanding the conditions that facilitate mutual benefits in data ecosystems and the mechanisms that ensure organizations can appropriate a fair share of the value creation they contribute to.
Keywords: M10; O30; 620; Data~ecosystems; Value~appropriation; Value creation; Data sharing